The Impact of Regional Government Financial Performance on Capital Expenditure - Jouzar Farouq Ishak (Jurnal ASET (Akuntansi Riset), 2021)
The purposes of this study is to examine the effect of regional government financial performance namely financial independence, fiscal decentralization, and financial efficiency on capital expenditure. The method used is multiple regression in provincial government in Indonesia in 2013-2020. Data for the study was collected from Directorate-General of Regional Fiscal Balance website. The result of the study indicate that financial decentralization and financial efficiency impact on capital expenditure. This show that provincial government increase local revenue and efficiency in regional spending.